Novel SNP Markers and Their Application in Low-Cyanide Cassava (Manihot esculenta crantz) Breeding Program - Chaicharoen, Adcharapun; Amawan, Suwaluk; Kansup, Jeeraporn; Sawwa, Aroonothai; Petchpoung, Krittaya (Trends in Sciences, 2023)
The major flaw of cassava is its indigenous cyanide. Traditional breeding program for diminishing cyanide in cassava take a long waiting time for harvesting cassava tubers to assess cyanide content. Genetic markers are useful for selection of good agricultural traits, which also applied in low-cyanide cassava breeding programs by detecting gene associate with cyanide content in cassava. Therefore, the objective of this study was to develop SNP markers to detect low cyanide trait in cassava. Genotype analysis was carried out using Genotyping by Sequencing (GBS) technology assembling with phenotype analysis. Then, the SNP markers associated with cyanide content were found. Afterward, the primers of SNP marker associated with cyanide content 2 positions were developed using tetra-primer ARMS-PCR techniques. S16_640082 and S16_735381 SNP markers on chromosome 16 showed potential ability of the selection of cassava varieties with cyanide content less than 250 mg HCN/kg fresh weight. The selection accuracy of S16_640082 and S16_735381 SNP markers was 73.33 and 76.64 %, respectively. These markers could be used in marker assisted selection (MAS) in cassava seedling. It substantially reduces cassava breeding programs cost and time. HIGHLIGHTS The major flaw of cassava is its indigenous cyanide. Up to our knowledge, there is rarely report on SNP marker related to cyanide content in Thai cassava population By performing genome wide association mapping (GWAS) to characterize the genome position related to HCN, 2 novel SNP markers associated with cyanide content were found The primers to detect the SNP markers were developed using tetra-primer ARMS-PCR techniques The markers showed ability of the selection of cassava varieties with cyanide content less than 250 mg HCN/kg fresh weight GRAPHICAL ABSTRACT